Peculiarities in the visual appearance of German cities – About locally specific routines and practices in urban design related governance - Brzenczek, Katharina; Wiegandt, Claus-Christian (ERDKUNDE, 2009)
The peculiar architectonic and spatial appearance of German cities cannot be sufficiently explained from their historical development and their economic performance alone. In our article we show therefore that the urban form, or townscape (Stadtgestalt) of four case study cities – Munich, Cologne, Bonn and Brunswick – is more adequately understood as the result of complex negotiation processes between a broad range of stakeholders. These processes reflect moreover the appreciation of a high quality built environment as well as the bargaining power of the key actors to introduce building design related aspects into the agenda. Also structures of societal interaction as well as institutionalised and normative regulatory systems play an important role. Recent years saw the emergence of new constellations between public and private stakeholders, with their respective roles and weight shifting within planning processes. Established, formal norms and planning procedures have been increasingly supplemented in different cities with new, informal rules and modes that are developed by the different municipalities and that help to account for their differing spatial appearances.